2017
DOI: 10.1111/aji.12765
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism of DNA methyltransferase 3B gene is a risk factor for recurrent spontaneous abortion

Abstract: DNMT3B rs1569686 gene polymorphism in women might be a genetic marker for the susceptibility to RSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The results of our study were similar to the previous studies carried out on Iranian and European populations with respect to the genotype and allele frequencies of DNMT3B rs2424913, DNMT3B rs1569686, DNMT3a rs7590760, DNMT1 rs2228611, and DNMT1 rs8101626 [18,20,30,31]. Likewise, the genotype and allele frequencies of DNMT3L rs2276248 in our study were consistent with those determined among healthy French women [32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our study were similar to the previous studies carried out on Iranian and European populations with respect to the genotype and allele frequencies of DNMT3B rs2424913, DNMT3B rs1569686, DNMT3a rs7590760, DNMT1 rs2228611, and DNMT1 rs8101626 [18,20,30,31]. Likewise, the genotype and allele frequencies of DNMT3L rs2276248 in our study were consistent with those determined among healthy French women [32].…”
Section: Discussionsupporting
confidence: 91%
“…НАУЧНАЯ СТАТЬЯ know, DNMT3B rs2424913, DNMT3A rs7590760, DNMT1 rs8101626, DNMT3L rs2276248, and DNMT3L rs2070565 polymorphisms have been analyzed only among women with various cancers and in male infertility [17-----19]. DNMT3B rs1569686 and DNMT1 rs2228611 have been analyzed in cancerous disease but only one study has genotyped them in Slovenian women with RPL [20]. SYCP3 T657C has been analyzed among Iranian and Japanese women with idiopathic RPL [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…DNA methyltransferases and TET are two key regulative gene families involved in DNA methylation and demethylation pathways, respectively, during both embryogenesis and spermatogenesis (Nettersheim et al, 2013;Barišić et al, 2017;Li et al, 2019). Despite their critical role in sperm methylation, the DNMT and TET genes have been poorly investigated in the context of male infertility (Uysal et al, 2016(Uysal et al, , 2019Tang et al, 2017Tang et al, , 2018.…”
Section: Dna Methylating and Demethylating Enzymesmentioning
confidence: 99%
“…A number of studies have demonstrated an association between genetic variants and the risk of RSA (27)(28)(29)(30). VEGF is among the established regulators of angiogenesis during pregnancy and has been associated with RSA (31,32).…”
Section: Resultsmentioning
confidence: 99%